Isu Pendidikan di Era Globalisasi “Fasilitas Pendidikan yang Kurang Merata” - Sukari, Sukari; Munzillah, Indiarti Muafiqoh (TSAQOFAH, 2025)
Indonesia is a country with many islands scattered around, from Sabang to Merauke. Each island has a different distance from the city center, has different natural or environmental conditions, has different languages, and different characteristics, so it is called Bhineka Tunggal Ika. Bhineka Tunggal Ika is the motto of the Indonesian nation which has different meanings but remains the same. In this era of globalization, there are several gaps, especially in remote areas. In many areas, especially in rural and remote areas, access to quality education is still very limited. Many children do not have the opportunity to study in adequate schools, while schools in urban areas are often equipped with modern facilities and better resources. This creates an injustice in students' learning opportunities and potential development.